Bras Basah Park (Institutional Knowledge at Singapore Management University, 2000)
Bras Basah Park in June 2000, looking toward Plaza by the Park (left) and the Singapore Art Museum (right) on Bras Basah Road. This is the site selected for Singapore Management University’s city campus .